2003
DOI: 10.1002/art.11296
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for coronary heart disease in women with systemic lupus erythematosus: The Toronto Risk Factor Study

Abstract: Women with SLE have a range of detectable coronary risk factors that are not fully reflected in the Framingham risk factor formula. These factors are likely to contribute to the loss of protection from CHD that has been observed in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
279
3
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(299 citation statements)
references
References 50 publications
9
279
3
8
Order By: Relevance
“…Cross-sectional studies of patients with differing degrees of disease activity and steroid dosages have generally demonstrated elevated mean triglyceride levels, while total cholesterol levels have been either normal or elevated. Similar variability in low-density lipoprotein (LDL) cholesterol and HDL cholesterol levels have been seen (13,16,23,24,27,(31)(32)(33). None of the studies published thus far have reported longitudinal data on lipid levels at fixed time points or evaluated large numbers of pediatric patients at presentation and at times of differing disease activity in order to better differentiate the effects of disease activity and steroid treatment.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Cross-sectional studies of patients with differing degrees of disease activity and steroid dosages have generally demonstrated elevated mean triglyceride levels, while total cholesterol levels have been either normal or elevated. Similar variability in low-density lipoprotein (LDL) cholesterol and HDL cholesterol levels have been seen (13,16,23,24,27,(31)(32)(33). None of the studies published thus far have reported longitudinal data on lipid levels at fixed time points or evaluated large numbers of pediatric patients at presentation and at times of differing disease activity in order to better differentiate the effects of disease activity and steroid treatment.…”
mentioning
confidence: 77%
“…Premature atherosclerosis, as demonstrated by the presence of abnormal carotid intima-media thickness and flow-mediated dilation, has been reported both in adult and pediatric patients with SLE (6,(9)(10)(11)(12)(13)(14)(15)(16). Although both traditional and nontraditional factors are important in the development of premature atherosclerosis in patients with SLE, dyslipoproteinemia, which is present in 30-73% of adult patients with SLE, plays a role in the development of atherosclerosis (2,10,(17)(18)(19)(20)(21)(22)(23)(24). To date, there have been few comprehensive lipid studies in pediatric patients with SLE (5,6,16,(25)(26)(27).…”
mentioning
confidence: 99%
“…Despite a high level of scientific interest in blood rheology and cardiovascular disease in the general population, little work has focused on the role of rheologic variables in lupus, a disease characterized by premature atherothrombotic events (6,7,34,35). Because traditional risk factors do not fully explain the high rate of atherosclerotic disease in patients with SLE, nontraditional risk factors warrant greater scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated atherosclerosis in particular is an important cause of premature morbidity and mortality, and the optimal way to prevent it is unknown. Although aggressive treatment of cardiac risk factors in patients with SLE is advocated (1)(2)(3)(4)(5), none of the prevention regimens or strategies have been critically evaluated. Clinical trials with the potential for important therapeutic benefit in the prevention of SLErelated atherosclerosis are therefore of paramount importance.…”
Section: Introductionmentioning
confidence: 99%